IMPLEMENTATION OF THE PROBLEM-BASED LEARNING MODEL TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS’ MATHEMATICAL NUMERACY LITERACY - Friska Situngkir (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Mathematics learning is frequently perceived as challenging by students due to the abstract nature of mathematical concepts and the limited integration of real-life contexts into classroom instruction. Consequently, there is a need for instructional approaches that effectively foster students' mathematical numeracy literacy and higher-order thinking skills. This study aimed to improve students' mathematical numeracy literacy through the implementation of the Problem-Based Learning (PBL) model. The study employed a Classroom Action Research (CAR) design conducted at Budi Murni 3 Junior High School, Medan, involving 30 eighth-grade students as research participants. The research was implemented in two action cycles, each consisting of four stages: planning, action, observation, and reflection. Data were collected using mathematical numeracy achievement tests and student activity observation sheets. The findings revealed that the implementation of the PBL model significantly enhanced students' mathematical numeracy literacy. The mean achievement score increased from 54 in the pre-action phase to 70 in Cycle I and further improved to 82 in Cycle II. Learning mastery also increased substantially from 26.7% to 86.7%. In addition, students' learning activities improved from 66.5% in Cycle I to 81.25% in Cycle II, indicating greater engagement throughout the learning process. These findings suggest that the Problem-Based Learning model is effective in improving students' mathematical numeracy literacy and promoting active participation in mathematics learning.